FAKTOR-FAKTOR YANG MEMENGARUHI PENGUNGKAPAN MODAL INTELEKTUAL - Hafza Neill Author; Agus Purwanto (Diponegoro Journal of Accounting, 2017)
This study examines the relationship of financial statement informativeness, firm size, financial performance, risk, growth, leverage with intellectual capital disclosure. The population in this study consists of all non financial and non property companies in Indonesia Stock Exchange in 2015. Total sample in this study is 256 samples of companies while the analysis test used by the writer is a model of multiple regression. The result shows a significant positive relationship between firm size, financial performance, and growth with intellectual capital disclosure. While, financial statement informativeness, risk, and leverage not significantly related with intellectual capital disclosure. This study contributes recent evidence concerning the factors influencing intellectual capital disclosure.